ANALISIS PROMOSI PENGGUNAAN MEDIA SOSIAL (INSTAGRAM, FACEBOOK, WHATSAPP) TERHADAP RESPON KONSUMEN PADA TOKO PUSAT OLEH – OLEH “RUMAH MADUMONGSO” KEDIRI - Puspa, Nova Vidya; Icshannudin; Suhardi, Suhardi (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
The objectives of this study are as follows: 1) To analyze promotions using Instagram social media to consumer responses at the central store by – by "Rumah Madumongso" Kediri. 2) To analyze promotions using Facebook social media to consumer responses at the central store by – by "Rumah Madumongso" Kediri. 3) To analyze promotions using WhatsApp social media to consumer responses at the central store by – by "Rumah Madumongso" Kediri. 4) to analyze promotions using social media Instagram, Facebook and WhatsApp to the response of consumers at the central store by – by "Rumah Madumongso" Kediri.  In the central store by -by "Rumah Madumongso" because it has consumers whose population is unlimited, the determination of the size of the number of research samples is set at 40 respondents, this is in accordance with Roschoe's theory.  The data collection technique uses accidental sampling, which is data taken to respondents when meeting in person. Furthermore, the data that has been collected is analyzed using multiple linear analysis. The results of this study are: 1). The influence of promotion using Instagram social media on consumer response at the oelh central store – by "Rumah Madumongso" Kediri. 2). The influence of promotion using Facebook social media on consumer response at the oelh central store – by "Rumah Madumongso" Kediri. 3). The influence of promotion using WhatsApp social media on consumer response at the oelh central store – by "Rumah Madumongso" Kediri. 4). The influence of promotion using social media Instagram, Facebook, and WhatsApp on consumer response at the oelh central store – by "Rumah Madumongso" Kediri.